THE TREND OF DIGITALIZATION IN RELIGIOUS COURTS: SOLUTIONS TO IMPROVE ACCESS TO JUSTICE FOR WOMEN IN DIVORCE CASES - Ulfah, Nasywaa; Henni, Henni; Kardi, Sukardi; Wibowo, Arif (Khatulistiwa, 2025)
The digitization of religious courts in Indonesia is a strategic solution to improve access to justice for women in divorce cases. This study aims to analyze digitization trends through the implementation of applications such as e-Court, which has successfully accelerated the case resolution process from an average of 6 months to 3 months, as well as empowering women by reducing bureaucratic barriers and dependence on intermediaries. However, the implementation of digitization still faces significant challenges, including disparities in information technology infrastructure, digital literacy gaps, and gender bias that has the potential to reinforce inequality in the judicial system. Using a qualitative research method based on a literature review, this study integrates socio-legal and maqasid syariah perspectives to evaluate the impact of digitization on women's access to justice. The results show that digital transformation has the potential to democratize access to justice if it is supported by inclusive application design, gender-responsive training for court officials, and legal education programs for the community. These findings emphasize the need to revise regulations related to e-Courts to ensure that the principles of substantive justice ('adl) and public interest (maslahah) can be achieved universally. (Supreme Court of Indonesia, 2024)